Reconciling Conflicting Norms: Addressing Patentability Challenges in Indonesia's Virtual Workspaces - Sudirman, Lu; Disemadi, Hari Sutra (JURNAL AKTA, 2024)
This research is done to analyze the nature of virtual workspace, which is increasingly becoming an important part of tech development around the world. Analysis is done to uncover the IPR elements of virtual workspaces and how these elements affect the patentability of virtual workspaces. Through the normative legal research method. Analysis of this research finds that the Indonesian Patent Law grossly undermines the capability and the importance of computer programming, through various normative restrictions. Instead, the Indonesian legal framework presents the Copyrights Law as the viable option, which in essence was made to protect creations that don’t necessarily involve problem solving, unlike the Patent Law. This finding is important as it fills the research gap on the analysis of virtual workspace not just as a cybersecurity topic but also as a possible patent, particularly in Indonesia’s intellectual property rights (IPR) legal framework.